2021
DOI: 10.1007/s10847-020-01039-1
|View full text |Cite
|
Sign up to set email alerts
|

Rapid temperature-assisted synthesis of nanoporous γ-cyclodextrin-based metal–organic framework for selective CO2 adsorption

Abstract: We present a rapid temperature-assisted synthesis route to synthesize cyclodextrin-based metalorganic frameworks (CD-MOFs) surfactant freely in a short time. The cubic crystals of CD-MOF with an average edge length of 10-15 m, specific surface area 775 m 2 g -1 and total pore volume 0.229 cm 3 g -1 were synthesized in much shorter time rather than conventional CD-MOFs. To show the efficiency of the synthesized CF-MOF as adsorbent of gas, the uptake of CO2 at different temperature and pressure demonstrated. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 47 publications
(43 reference statements)
1
16
0
Order By: Relevance
“…Microporous carbon nanospheres have also been prepared from β-CD by solvothermal carbonization in o-dichlorobenzene with the presence of various concentrations of p-toluene sulfonic acid (PTSA) [ 58 ]. For the thermal activation, a rapid temperature-assisted synthesis has been reported to improve the porous structure of the cyclodextrins for CO 2 adsorption [ 59 ]. Regarding the pyrolysis stages [ 50 ], apparent activation energy and pyrolysis kinetics of the cyclodextrins [ 60 ] have been preliminarily investigated in some literature.…”
Section: Introductionmentioning
confidence: 99%
“…Microporous carbon nanospheres have also been prepared from β-CD by solvothermal carbonization in o-dichlorobenzene with the presence of various concentrations of p-toluene sulfonic acid (PTSA) [ 58 ]. For the thermal activation, a rapid temperature-assisted synthesis has been reported to improve the porous structure of the cyclodextrins for CO 2 adsorption [ 59 ]. Regarding the pyrolysis stages [ 50 ], apparent activation energy and pyrolysis kinetics of the cyclodextrins [ 60 ] have been preliminarily investigated in some literature.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the storage of single target compounds, CD-MOF based materials also show high potential in the selective separation of gases, hydrocarbons, isomers, benzenoid compounds and other mixtures. 90,101,158,159,169,[205][206][207][208] Thanks to the tailorable pore sizes and uncoordinated, weakly nucleophilic primary hydroxyl groups of CD-MOFs they could be significant even in large-scale industrial processes, for instance during acetylene (C 2 H 2 ) gas synthesis where minor fractions of CO 2 are formed as a side-product. To remove trace amounts of CO 2 from a mixture with C 2 H 2 , Li et al synthesized a K-and a Rb-g-CD-MOF which showed inverse adsorption abilities.…”
Section: Storage Separation and Removal Of Chemicalsmentioning
confidence: 99%
“…On the other hand, amino groups were introduced to the β-cyclodextrin-based metal–organic framework to enhance the carbon dioxide capture capacity of the β-cyclodextrin-based metal–organic framework from 1.2 to 12.3 cm 3 /g at 273 K as well as enhancing the water stability from 18 to 24 mg/mL, and this is due to the polar nature of β-cyclodextrin (Xu et al 2020 ). Moreover, a γ-cyclodextrin-based metal–organic framework with crystalline morphology and surface area reaching 775 m 2 /g and a pore volume of 0.229 cm 3 /g was synthesized by vapor diffusion method at high temperature and pressure (Hamedi et al 2021 ). Hamedi et al ( 2021 ) found that the carbon dioxide capture increased with raising pressure and lowering.…”
Section: Potential Applications Of Cyclodextrin-based Metal–organic F...mentioning
confidence: 99%
“…Moreover, a γ-cyclodextrin-based metal–organic framework with crystalline morphology and surface area reaching 775 m 2 /g and a pore volume of 0.229 cm 3 /g was synthesized by vapor diffusion method at high temperature and pressure (Hamedi et al 2021 ). Hamedi et al ( 2021 ) found that the carbon dioxide capture increased with raising pressure and lowering. Besides, the maximum carbon dioxide capture of γ-cyclodextrin-based metal–organic framework reached as high as 326 mg/g at 303 K. Moreover, Wang et al ( 2018 ) prepared γ-cyclodextrin-based metal–organic framework-potassium with excellent adsorption capacity for formaldehyde.…”
Section: Potential Applications Of Cyclodextrin-based Metal–organic F...mentioning
confidence: 99%